(3GdCOGI GdGbJUGOjI hOhQgG aj GdSjGSI GdNGQLjI dOhdI GdGeGQGJ GdYQHjI GdeJMOI(B:s (3OQGSI JMdjdjI (B/s - (3GdMeGOj(B, (3egQIs ((3CHhXHj (B- (3OhdI GdGeGQGJ GdYQHjI GdeJMOI(B:s (3eQcR GdGeGQGJ ddOQGSGJ hGdHMhK GdGSJQGJjLjI(B,s, 2022)
(3oJnYoqO GdCOGI GdGbJUGOjI efP GdCRd ef GdYhGed GdeMOOI ddSdhc GdSjGSj GdNGQLj dOhdI eG JLGg OhdmI CNQi(B. (3hdWGdeG LPH ehVhY gPg GdbhI GdfGYeI, hOhQgG aj fbd CgOGa GdSjGSI GdNGQLjI ef MjR GdJNWjW Edi eLGd GdJfajP, GgJeGe NHQGA GdYdGbGJ GdOhdjI efP JSYjfjGJ GdbQf GdefUQe; GdYbO GdPj QSe efYWkaG dYhdeI GdYdGbGJ GdGbJUGOjI hGJLGggG fMh JcKja GdJYGed HeG jJVefg gPG Gdeaghe; ef JYGhf hJfGaS Hjf eNJda GdCWQGa GdOhdjI, hYdi eNJda GdeSJhjGJ(B. (3heY GNJdGa GdCOhGJ, GdJj JSJNOegG Ohd GdYGde, hChdhjI JQJjHgG, aj JWHjb CLfOI GdSjGSI GdNGQLjI, ef COhGJ GbJUGOjI Ch YScQjI Ch OHdheGSjI Ch EYdGejI Ch eRjL efgG, JgOa gPg GdOQGSI Edi EHQGR GdCOGI GdGbJUGOjI hOhQgG aj JfajP GdSjGSI GdNGQLjI Vef oeMpqOnOjf(B: (3ecGfqj, GdSjGSI GdNGQLjI dOhdI GdEeGQGJ GdYQHjI GdeJMOI; hReGfqj, Hjf YGej (B1971 (3h(B2016. (3EVGakI Edi EKHGJ CgejI gPg GdCOGI aj JhWjO YdGbGJ OhdI GdEeGQGJ eY Ohd GdYGde, hJMbjb GdGSJbQGQ dSjGSJgG GdNGQLjI(B. (3afXkQG Edi haQI GdehGQO GdWHjYjI, ef famW hZGmR hZjQgeG, aj OhdI GdEeGQGJ, heG UGMH Pdc ef edGAI GbJUGOjI; cGfJ QDjI McGegG, GHJOGkA ef GdCH GdeDSS GdTjN RGjO Hf SdWGf Bd fgjGf, WjH Gddg KQGg, hUhkdG Edi UGMH GdSeh GdTjN NdjaI Hf RGjO Bd fgjGf, QFjS GdOhdI, MaXg Gddg, JJhLg Edi GSJNOGe GdCOGI GdGbJUGOjI cCMO oSHd GdhMOI GdSjGSjI, hJHfJ OhdI GdEeGQGJ fgkLG GJSe HhaQI GdeSGYOGJ GdGbJUGOjI GdNGQLjI, HTJi CfhGYgG, ef eGdjI hSdYjI hNOejI; MJi hUdJ Edi ehbY eJbOe Ydi oSnqde GdYdGbGJ GdEbdjejI hGdOhdjI(B. (3ceG oJYpqQa gPg GdOQGSI CHQR GdfeGPL GdfGLMI, GdJj GSJWGYJ OhdI GdEeGQGJ, ef NdGd GdeYhfGJ hGdbQhV hGdeSGYOGJ hGdGSJKeGQGJ, hZjQgG ef echfGJ GdCOGI GdGbJUGOjI, JfajP CgOGa SjGSJgG GdNGQLjI, hJhVM cja COi GdGSJNOGe GdMcje dgPg GdecqhfGJ Edi fTQ eHGOF GdJSGeM hGdJYGjT hGdJhGab hGdSdGe hGdGfJaGY, hfJL efgG JMbjb GdGSJbQGQ hGdCeGf hGdeUGdM GdeTJQcI(B. (3hEVGakI Edi Pdc oJbqOe GdOQGSI LedkI ef GdfJGFL hGdJhUjGJ hGdMdhd, GdJj jecf Cf JSge aj JYXje OhQ gPg GdCOGI aj JfajP GdSjGSI GdNGQLjI dOhdI GdEeGQGJ HTcmd NGU, hddOhd GdeTGHgI dgG ef MjK GdehGQO hGdMLe GdLZQGaj HTcmd YGe(B.s
Keywords: (3GdEeGQGJ GdYQHjI GdeJMOI (B-- (3YdGbGJ NGQLjIs; (3GdEeGQGJ GdYQHjI GdeJMOI (B-- (3SjGSI NGQLjIs; (3GdEeGQGJ GdYQHjI GdeJMOI (B-- (3GdGMhGd GdGbJUGOjI (B-- 1971-2016s